Psychosoziale Risikofaktoren für chronischen Rückenschmerz in der Allgemeingesellschaft und im Leistungssport - Hasenbring, Monika; Levenig, Claudia; Hallner, Dirk; Schiltenwolf, Marcus; Pfeifer, Ann-Christin (Der Schmerz, 2018)
BackgroundLumbar back pain and the high risk of chronic complaints is not only an important health concern in the general population but also in high performance athletes. In contrast to non-athletes, there is a lack of research into psychosocial risk factors in athletes. Moreover, the development of psychosocial screening questionnaires that would be qualified to detect athletes with a high risk of chronicity is in the early stages. The purpose of this review is to give an overview of research into psychosocial risk factors in both populations and to evaluate the performance of screening instruments in non-athletes.MethodsThe databases MEDLINE, PubMed, and PsycINFO were searched from March to June 2016 using the keywords “psychosocial screening”, “low back pain”, “sciatica” and “prognosis”, “athletes”. We included prospective studies conducted in patients with low back pain with and without radiation to the legs, aged ≥18 years and a follow-up of at least 3 months.ResultsWe identified 16 eligible studies, all of them conducted in samples of non-athletes. Among the most frequently published screening questionnaires, the Örebro Musculoskeletal Pain Screening Questionnaire (ÖMPSQ) demonstrated a sufficient early prediction of return to work and the STarT Back Screening Tool (SBT) revealed acceptable performance predicting pain-related impairment. The prediction of future pain was sufficient with the Risk Analysis of Back Pain Chronification (RISC-BP) and the Heidelberg Short Questionnaire (HKF).ConclusionPsychosocial risk factors of chronic back pain, such as chronic stress, depressive mood, and maladaptive pain processing are becoming increasingly more recognized in competitive sports. Screening instruments that have been shown to be predictive in the general population are currently being tested for suitability in the German MiSpEx research consortium.